Polycrystalline films of phosphors Cd(1-x-y-z) (CuyAgz) ZnxS on the silicon substrate with the silicon carbide buffer layer: structure and properties - Sergeeva, N.M.; Bogdanov, S.P.; Redkov, A.V. (Peter the Great St.Petersburg Polytechnic University, 2019)
Polycrystalline phosphor film Cd(1-x-y-z) (CuyAgz) ZnxS was grown on the surface of the Si/nano-SiC heterostructure obtained by the unique method of substitution of atoms. The structural, phonon (vibrational) properties of the film, as well as its morphology were studied. X-ray phase analysis (XRD) showed that the phase composition is represented by a matrix of solid solution of cubic syngony and impurity phases formed during precipitation: sodium sulfate (Na2SO4) of orthorhombic syngony and sodium cadmium sulfide (Na6Cd7S10) of monoclinic syngony. The Raman spectroscopy (RS) method confirmed the components of the polycrystalline phosphor film, including its phase composition, determined by the X-ray phase analysis method.